Effect of anti-aging systems on thermal stability of bromobutyl rubber - DENG Zheng-wei, LUO Hua-lin, DU Jian-qiang (Hecheng xiangjiao gongye)
The effect of heat treatment temperature and time on Mooney viscosity of different bromobutyl rubber (BIIR) was investigated, the effect of different types and addition amounts of antioxidant and stabilizers at heat treatment temperature of 120 ℃ on bromine content and microstructure of BIIR was studied and the storage period of BIIR was calculated based on the time-temperature equivalence principle. The results showed that compared with sample 1, the total antioxidant content was significantly lower, the stabilizer content was higher, and the bromine content and type Ⅱ structure content were lower in sample 2. After heat treatment for a certain period of time, sample 2 showed the coexistence phenomenon of degradation and cross-linking, the thermal oxygen aging degradation of sample 2 was obvious than that of sample 1, and the higher the temperature was, the obvious the degradation phenomenon was. When the bromine content of BIIR decreased, the microstructure transformed from type Ⅱ to type Ⅲ, and the debromination reaction led to a significant increase in the content of type Ⅳ and V structure. According to the time-temperature equivalence principle, it was deduced that the stability of sample 2 under storage conditions was better than that of sample 1, However, the longer residence time at high temperature in the post-treatment process was not conducive to the stable storage of sample 2.